In vitro antifungal activity of extracts obtained from Hypericum perforatum adventitious roots cultured in a mist bioreactor against planktonic cells and biofilm of Malassezia furfur. Issue 5 (3rd March 2016) - Simonetti, Giovanna; Tocci, Noemi; Valletta, Alessio; Brasili, Elisa; D'Auria, Felicia Diodata; Idoux, Alicia; Pasqua, Gabriella
Abstract : Xanthone-rich extracts from Hypericum perforatum root cultures grown in a Mist Bioreactor as antifungal agents against Malassezia furfur . Extracts of Hypericum perforatum roots grown in a bioreactor showed activity against planktonic cells and biofilm of Malassezia furfur . Dried biomass, obtained from roots grown under controlled conditions in a ROOTec mist bioreactor, has been extracted with solvents of increasing polarity (i.e. chloroform, ethyl acetate and methanol). The methanolic fraction was the richest in xanthones (2.86 ± 0.43 mg g − 1 DW) as revealed by HPLC. The minimal inhibitory concentration of the methanol extract against M. furfur planktonic cells was 16 μg mL − 1 . The inhibition percentage of biofilm formation, at a concentration of 16 μg mL − 1, ranged from 14% to 39%. The results show that H. perforatum root extracts could be used as new antifungal agents in the treatment of Malassezia infections. Abstract :